Local variations in the distribution and prevalence of Borrelia burgdorferi sensu lato genomospecies in Ixodes ricinus ticks. - Kirstein, F (1997)
Unfed nymphal and adult Ixodes ricinus ticks were collected from five locations within the 10,000-ha Killarney National Park, Ireland. The distribution and prevalence of the genomospecies of Borrelia burgdorferi sensu lato in the ticks were investigated by PCR amplification of the intergenic spacer region between the 5S and 23S rRNA genes and by reverse line blotting with genomospecies-specific oligonucleotide probes. The prevalence of ticks infected with B. burgdorferi sensu lato was significantly variable between the five locations, ranging from 11.5 to 28.9%. Four genomospecies were identified as B. burgdorferi sensu stricto, Borrelia afzelii, Borrelia garinii, and VS116. Additionally, untypeable B. burgdorferi sensu lato genomospecies were identified in two nymphs. VS116 was the most prevalent of the genomospecies and was identified in 50% of the infected ticks. Prevalences of B. garinii and B. burgdorferi sensu stricto were similar (17 and 18%, respectively); however, significant differences were observed in the prevalence of these genomospecies in mixed infections (58.8 and 23.5%, respectively). Notably, the prevalence of B. afzelii was low, comprising 9.6 and 7.4%, respectively, of single and mixed infections. Significant variability was observed in the distribution and prevalence of B. burgdorferi sensu lato genomospecies between locations in the park, and the diversity and prevalence of B. burgdorferi sensu lato genomospecies was typically associated with woodland. The distributions of B. burgdorferi sensu lato genomospecies were similar in wooded areas and in areas bordering woodland, although the prevalence of B. burgdorferi sensu lato infection was typically reduced. Spatial distributions vegetation composition, and host cenosis of the habitats were identified as factors which may affect the distribution and prevalence of B. burgdorferi sensu lato genomospecies within the park.